IMPLEMENTASI SISTEM OPERASI LINUX FEDORA 22 SEBAGAI WEBSERVER DALAM MENDUKUNG LAYANAN SISTEM TERDISTRIBUSI - R. Fanri Siahaan; Parulian Sirait (STMIK Pelita NUsantara, 2017)
webserver is software that functions accept http or https request in the form of a web page that is generally shaped html document. Webserver most widely used today is apache. Apache was first designed for the UNIX operating system, but the next version of apache issued several applications that can be run on WINDOWS. Linux is known to the operating system that was originally devoted to servers, Linux is known to the security of data access, so that linux is still known as the operating system that has the ability to penetrate and protect a network. therefore many major networking vendors use Linux as an operating system for servers they use, because Linux offers that are hard to penetrate security and speed in processing the data.